Differential Scanning Calorimetry of Fish and Shellfish Meat - Uddin, Musleh; Uddin Ahmed, Moin; Jahan, Praveen; Sangu, Romanee (Asian Journal of Chemistry, 2010)
Thermal properties of five fish and shellfish meat proteins were studied using the differential scanning calorimetry (DSC). As a result, the main three endothermic peaks were shown for both fish and shellifish meats. The first, second and third peaks corresponded to myosin, sarcoplasmic proteins/or actomyosin complex and actin. The transition temperature (Tm) of fish and shellfish actin was lower than those of mammals. Saury and scallop meat showed a small endothermic peak within the temperature range of 36-39°C which corresponded by transition temperature of myosin tail and defined as low temperature endothermic peak (LTEP).